Serous cystadenofibroma of ovary mimicking malignancy: a case report and review of diagnostic challenges - Kalpana, B.; Anand, Aishwina; Balamurugan, S. G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Ovarian cystadenofibroma is a rare benign epithelial tumour composed of both glandular and fibrous stromal elements. Although benign, its imaging features mimic those of malignant neoplasms, posing diagnostic and therapeutic challenges. We report a case of 31-year-old nulliparous woman who presented with heavy menstrual bleeding. Clinical examination revealed right adnexal fullness and imaging studies demonstrated a complex multiloculated right ovarian cyst measuring approximately 5cm. a provisional diagnosis of complex ovarian neoplasm was made. Patient underwent right ovarian cystectomy. Histopathological examination confirmed the diagnosis of benign serous cystadenofibroma.